Independent Fiscal Councils : Recent Trends and Performance - Beetsma, Roel (IMF Working Papers; Working Paper ;, 2018)
Countries increasingly rely on independent fiscal councils to constrain policymakers' discretion and curb the bias towards excessive deficits and pro-cyclical policies. Since fiscal councils are often recent and heterogeneous across countries, assessing their impact is challenging. Using the latest (2016) vintage of the IMF Fiscal Council Dataset, we focus on two tasks expected to strengthen fiscal performance: the preparation or assessment of forecasts, and the monitoring of compliance with fiscal rules. Tentative econometric evidence suggests that the presence of a fiscal council is associated with more accurate and less optimistic fiscal forecasts, as well as greater compliance with fiscal rules.